2014
DOI: 10.1371/journal.pone.0107353
|View full text |Cite
|
Sign up to set email alerts
|

Combining Structural Modeling with Ensemble Machine Learning to Accurately Predict Protein Fold Stability and Binding Affinity Effects upon Mutation

Abstract: Advances in sequencing have led to a rapid accumulation of mutations, some of which are associated with diseases. However, to draw mechanistic conclusions, a biochemical understanding of these mutations is necessary. For coding mutations, accurate prediction of significant changes in either the stability of proteins or their affinity to their binding partners is required. Traditional methods have used semi-empirical force fields, while newer methods employ machine learning of sequence and structural features. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 74 publications
(107 reference statements)
2
93
0
Order By: Relevance
“…In line with experimental observations, it was found that naturally occurring mutations decrease binding affinity of spermine synthase homo-domain causing Snyder-Robinson syndrome [23], while enhancement of the binding between CLIC2 protein and ryanodine receptor causing an X-linked channelopathy [15, 18]. Genomic-scale investigations were also carried out with combined efforts of machine learning and statistical potentials [55]. Molecular dynamics studies, being computationally expensive, were applied to study specific cases only [56], including disruption of salt bridges between protein and substrate [57].…”
Section: Impact Of Mutations On Protein-protein Protein-ligand and Pmentioning
confidence: 98%
“…In line with experimental observations, it was found that naturally occurring mutations decrease binding affinity of spermine synthase homo-domain causing Snyder-Robinson syndrome [23], while enhancement of the binding between CLIC2 protein and ryanodine receptor causing an X-linked channelopathy [15, 18]. Genomic-scale investigations were also carried out with combined efforts of machine learning and statistical potentials [55]. Molecular dynamics studies, being computationally expensive, were applied to study specific cases only [56], including disruption of salt bridges between protein and substrate [57].…”
Section: Impact Of Mutations On Protein-protein Protein-ligand and Pmentioning
confidence: 98%
“…Free energy differences upon binding calculated via thermodynamic integration and free energy perturbation approaches combined with molecular dynamics simulations are computationally expensive, particularly for large-scale protein complexes [41]. Therefore, many have developed in silico tools as a fast alternative to estimate ΔΔG using statistical energy functions based on known protein structures [4244] and/or coupling with machine learning tools using training sets [4547]. However, these calculations can be rather inaccurate, because local structural changes upon mutations are generally neglected [48,49].…”
Section: Evolutionary and Structural Approaches For Prediction Of Dismentioning
confidence: 99%
“…Ideally, such datasets would include negative data in order to robustly train predictive models and advance the field in the direction of data driven computational predictions, e.g., available protein thermostability benchmark datasets have allowed machine learning to be applied, resulting in accurate thermostability predictions. 18 Fortunately, data from multiple experiments for developability on 137 diverse mAbs in clinical trials or approved at the time of publication have been made available, 2 and a series of 31 adnectin variants with percent inclusion body data has recently been published. 19 …”
Section: Introductionmentioning
confidence: 99%